Hybrid environments for universities - Liedtke, Bettina (Waxmann Verlag, 2020)
This publication is the result of an international and interdisciplinary expert meeting at Technische Universität Berlin, in March 2020. The aim of the expert meeting was to collaboratively write and publish a book, within five days, on the central question: Which organizational structures and processes at universities support a strategic as well as innovative campus development? As experts with an interdisciplinary background including the social sciences, public real estate, urban planning, architecture and landscape architecture, we could examine the question from a holistic perspective and gain new insights. The resulting manifesto states necessary strategies and action fields to make universities as hybrid environments innovative and sustainable. It addresses all decision makers - executives, practitioners and contributors equally - who are facing the challenge of limited resources and are embracing the opportunities to do more with less.